Female Sleuths in Chick Lit: Girl Power in Maya Calica’s Undercover TaiTai and Gemma Halliday’s Killer in High Heels - Samillano-Trujillo, J (KnE Social Sciences, 2018)
The representation of women in the waves of feminism swifts into more empowered women in the era of post feminism. Chick lit as subgenre of postfeminist fiction depicts female protagonists who enjoy freedom and feminity. It is a genre that highlighted girl power. This paper analysed the represented identity of female sleuths and the aspect of girl power portrayed in the chick lit novels of Maya Calica’s Undercover TaiTai and Gemma Halliday’s Killer in High Heels. It was found out that female protagonists represent women who are tough, wear social masquerade, amateur sleuths, and celebrate feminity to influence others. They used their individual power, beauty and sexual attractiveness power to achieve their goals in life personally and professionally. The representations of girl power in these chick lit novels give space for women to celebrate their femininity and gain their power at the same time. Keywords: Chick lit genre, Female sleuth, Girl power, Postfeminist.